Screening and In Vitro Evaluation of Potential Plasmodium falciparum Leucyl Aminopeptidase Inhibitors - Chaudhary, Meenakshi; Singh, Vineeta; R. Anvikar, Anup; Sahi, Shakti (Current Computer - Aided Drug Design, 2016)
Background: Plasmodium falciparum leucyl aminopeptidase (PfA-M17) regulates the intracellular pool of amino acids required for the growth and development of parasites. Thus, PfA-M17 is a promising target for anti-malarial drug development. Method: In the present study, structure-based drug design was used to identify novel PfA-M17 inhibitors, which were subsequently validated by in vitro PfA-M17 and human LAP3 enzyme inhibition assay. A library of 3,147,882 compounds was screened using receptor-based virtual screening against the active site of PfA-M17, and three levels of accuracy were used: high-throughput virtual screening, gridbased ligand docking with energetics (Glide standard precision) and Glide extra precision. Results: Seventeen screened compounds were selected and tested in the rPfA-M17 enzyme inhibition assay. Of these nine compounds were found to be effective inhibitors. To test the target activity, all nine PfA-M17 inhibitors were tested against rhLAP3, the human homolog of PfA-M17. One compound (compound 2) was found to be moderately effective against PfA-M17 (Ki = 287 μM) with limited inhibitory activity against hLAP3 (Ki of 4,464 μM). Subsequently, induced fit docking and pharmacophore modelling were used to further understand more precise ligand–protein interactions in the protein–inhibitor complexes. Conclusion: Among the 9 effective PfA-M17 inhibitors, 5 compounds were found effective in the P. falciparum schizont maturation inhibition (SMI) assay. A good correlation (r =0.83) was observed between the rPfA-M17 enzyme inhibition concentration and SMI assay.
Keywords: molecular docking